The evolution of an environmentally friendly hatchery technology for udang galah, the king of freshwater prawns and a glimpse into the future of aquaculture in 21st century - Ang, Kok Jee (Universiti Pertanian Malaysia, 1995)
This lecture consists of two part. Part one summaries the research on Macrobrachium rosenbergii conducted in Universiti Pertanian Malaysia since 1977 highlighting its seed production technology. The second part contains some thoughts/perceptions on the direction/trend of aquaculture development in the 21st century.